Das ist der HAMMER: consistent new physics interpretations of semileptonic decays - Florian U. Bernlochner; Stephan Duell; Zoltan Ligeti; Michele Papucci; Dean J. Robinson (European Physical Journal C: Particles and Fields, 2020)
Abstract Precise measurements of $$b→ cτ \bar{ν }$$ b → c τ ν ¯ decays require large resource-intensive Monte Carlo (MC) samples, which incorporate detailed simulations of detector responses and physics backgrounds. Extracted parameters may be highly sensitive to the underlying theoretical models used in the MC generation. Because new physics (NP) can alter decay distributions and acceptances, the standard practice of fitting NP Wilson coefficients to SM-based measurements of the $$R(D^{(*)})$$ R ( D ( ∗ ) ) ratios can be biased. The newly developed Hammer software tool enables efficient reweighting of MC samples to arbitrary NP scenarios or to any hadronic matrix elements. We demonstrate how Hammer allows avoidance of biases through self-consistent fits directly to the NP Wilson coefficients. We also present example analyses that demonstrate the sizeable biases that can otherwise occur from naive NP interpretations of SM-based measurements. The Hammer library is presently interfaced with several existing experimental analysis frameworks and we provide an overview of its structure.